The determinants of higher education institutions' (HEIs) sustainability reporting - Maylia Pramono Sari; Faisal Faisal; Puji Harto (Cogent Business & Management, 2023)
This study analyses the relationship between sustainability performance, convention signatures, sustainability offices, sustainability research, teaching programs, student clubs, financial statements, and the extent of sustainability reporting in higher education institutions (HEIs). The sample of this study was 153 unit of analysis of 57 HEIs which are registered in the Global Reporting Initiative database during the period 2010-2020. Descriptive, content, and multivariate regression analysis were used to analyze the data and test the hypotheses. The level of sustainability performance, convention signatures, sustainability offices, sustainability research, teaching programs, student clubs, financial statements have a significant effect on the extent of sustainability reporting. Moreover, the random effect model is the best approach for estimating the model. The study contributes to a better understanding of the determinants of HEIs sustainability reporting. Several previous studies only used one theoretical lens. The originality of this research is using a metatheoretical approach, namely stakeholder and legitimacy theory. The theoretical implication of these findings is that the combination of legitimacy and stakeholder theory is able to explain more broadly the model of HEIs sustainability reporting. Policymakers such as the government and other key stakeholders can use these findings as the basis for assessing an educational institution's sustainability performance.
Keywords: 650; higher education institutions; legitimacy theory; stakeholder theory; sustainability performance; sustainability reporting